GIS applications in agriculture. - Clay, Sharon A. (GIS applications in agriculture., 2011)
While many "alien" plant and animal species are purposefully introduced into new areas as ornamentals, livestock, crops, and even pets, these species can escape into other areas and threaten agricultural and native ecosystems causing economic and environmental harm, or harm to human health. Increasingly, scientists are using Geographic Information Systems (GIS) to track and manage the invaders, mitigate the potential rate of spread and level of impact, and protect the native economy and ecosystem. Beginning with an introduction to the use of GIS technology to capture, store, analyze.